Effect of stretching duration on active and passive range of motion in the lower extremity - Roberts, J. M.; Wilson, K. (British Journal of Sports Medicine, 1999)
Es wird der Einfluss unterschiedlicher Stretchingdauer (5 oder 15 sec) auf den aktiven und passiven Bewegungsumfang der unteren Extremität während eines 5wöchigen Beweglichkeitstrainingsprogramms untersucht. Ergebnis: Das Halten der Dehnung über 15 sec resultiert im Vergleich zu 5 sec in einer größeren Verbesserung des aktiven Bewegungsumfangs. Der passive Bewegungsumfang wird durch die Haltezeit nicht signifikant beeinflusst. OBJECTIVES: To investigate the effect of different durations of stretching (five or 15 seconds) on active and passive range of motion (ROM) in the lower extremity during a five week flexibility training programme. METHOD: Twenty four university sport club members (19 men, five women), with a mean (SD) age of 20.5 (1.35) years, were randomly assigned to one of three groups (two treatment and one control). The two treatment groups participated in a static active stretching programme three times a week for a five week period, holding each stretch for a duration of either five or 15 seconds. The total amount of time spent in a stretched position was controlled. The five second group performed each stretch nine times and the 15 second group three times resulting in a total stretching time of 45 seconds for both groups for each exercise. The control group did not stretch. Active and passive ROM were determined during left hip flexion, left knee flexion, and left knee extension before and after the training programme using an inclinometer. RESULTS: Two factor within subject analysis of variance indicated no significant difference in ROM before and after the training programme for the control group. However, significant improvements in active and passive ROM (p < 0.05) were shown in both treatment groups after the five week training programme. Two factor analysis of variance with repeated measures and post hoc analysis showed significant differences between the treatment groups and the control group for the improvements observed in active (p < 0.05) and passive (p < 0.05) ROM. The five and 15 second treatment groups did not differ from one another when ROM was assessed passively, but significant differences were apparent for active ROM, with the 15 second group showing significantly greater improvements (p < 0.05) than the five second group. CONCLUSION: These findings suggest that holding stretches for 15 seconds, as opposed to five seconds, may result in greater improvements in active ROM. However, sustaining a stretch may not significantly affect the improvements gained in passive ROM.